THE INFLUENCE OF PRODUCT QUALITY, PRICE PERCEPTION AND LOCATION ON CUSTOMER SATISFACTION AT WARMINDO BAROKAH KEDUNGMUNDU - Ramadhan, Gilang Amar; Soliha, Euis (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
The purpose of this research is to analyze the influence of product quality, price perception and location on customer satisfaction at Warmindo Barokah Kedungmundu. The population in this study were Warmindo Barokah Kedungmundu customers. The research method used was purposive sampling. The data used were 99 respondents using the questionnaire data collection method. Data analysis uses instrument tests, multiple linear analysis and model tests. The results from respondent data prove that product quality has a positive effect on customer satisfaction. Price perception has no effect on customer satisfaction and location has a positive effect on customer satisfaction.